NADPH oxidase inhibitor improves outcome of mechanical reperfusion by suppressing hemorrhagic transformation. (13th April 2016) - Tuo, Yong-Hua; Liu, Zhong; Chen, Jian-Wen; Wang, Qing-Yuan; Li, Song-Lin; Li, Ming-Chang; Dai, Gang; Wang, Jin-Shan; Zhang, Yong-Li; Feng, Lei; Shi, Zhong-Song
Abstract : Background: Severe hemorrhagic transformation (HT) after mechanical thrombectomy predicts a poor clinical outcome in acute ischemic stroke. To better understand the mechanism of HT, we investigated the role of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) in HT after reperfusion during acute stroke and whether NOX2/4 inhibitor VAS2870 reduces reperfusion-induced HT after mechanical recanalization. Methods: A model of reperfusion-induced HT was established in rats (n=182) with hyperglycemic challenge and 5 h middle cerebral artery occlusion followed by 19 h reperfusion. NOX inhibitor VAS2870 was delivered intravenously 30 min before reperfusion. Infarct volume, brain water content, HT, neurological score, mortality rate, blood–brain barrier (BBB) damage, neuronal apoptosis, and reactive oxygen species were determined at 24 h after cerebral ischemia. The expressions of NOX1, NOX2, NOX4, and BBB-associated proteins were measured. Results: NOX2 and NOX4 upregulation and severe HT were observed in hyperglycemic rats after cerebral ischemia/reperfusion. VAS2870 suppressed oxidative stress, neuronal apoptosis, and NOX2/4 upregulation in the ischemic hemisphere. VAS2870 reduced infarct volume (17.2±5.3% vs 37.4±9.2%, p<0.01) and the frequency of reperfusion-induced parenchymal hematoma (29.7% vs 59.5%, p<0.05) at 24 h after ischemia compared with the ischemia/reperfusion group. VAS2870 attenuated brain edema and reduced reperfusion-induced BBB breakdown, resulting in improved neurological outcome (neurological deficit score 1.43±0.50 vs 2.43±0.93, p<0.001) and reduced mortality (11.9% vs 64.1%, p<0.001). Conclusions: NOX2 and NOX4 may mediate HT in rats with large vessel stroke after mechanical reperfusion. Infusion of NOX inhibitor VAS2870 before mechanical thrombectomy represents a novel adjunctive therapeutic strategy to prevent reperfusion-induced HT and improve outcome of acute stroke treatment.